Fibronectin modulates thymocyte-thymic epithelial cell interactions following Trypanosoma cruzi infection - Oliveira, Désio Aurélio Farias de (2013)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Pesquisas sobre o Timo. Rio de Janeiro, RJ, Brasil.